A theoretical model to determine intercalation entropy and enthalpy: Application to lithium/graphite - Perassi, Eduardo Marcelo (2016)
Intercalation compounds play a fundamental role to increase the capabilities of electrochemical cells to store energy. A new computational model is developed to calculate the intercalation entropy and enthalpy in electrochemical intercalation compounds. The new methodology is applied to the intercalation of lithium ions into graphite, finding a good agreement with experimental measurements. The main features of the experimental data are correctly reproduced, including the step in the intercalation entropy and enthalpy for the stage II to stage I transition.